2023
DOI: 10.1200/jco.22.01565
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy or Surgery of the Axilla After a Positive Sentinel Node in Breast Cancer: 10-Year Results of the Randomized Controlled EORTC 10981-22023 AMAROS Trial

Abstract: Clinical trials frequently include multiple end points that mature at different times. The initial report, typically based on the primary end point, may be published when key planned co-primary or secondary analyses are not yet available. Clinical Trial Updates provide an opportunity to disseminate additional results from studies, published in JCO or elsewhere, for which the primary end point has already been reported. PURPOSE The European Organisation for Research and Treatment of Cancer 10981-22023 AMAROS tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
109
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(111 citation statements)
references
References 14 publications
0
109
0
2
Order By: Relevance
“…Several objective BCRL detection methods have been applied. In the AMAROS trial, an increase in arm circumference 15 cm above and below the medial epicondyle by more than 10% compared with the contralateral arm was defined as BCRL [ 3 ]. The DBCG trial (NCT02384733) also used the same measurement [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several objective BCRL detection methods have been applied. In the AMAROS trial, an increase in arm circumference 15 cm above and below the medial epicondyle by more than 10% compared with the contralateral arm was defined as BCRL [ 3 ]. The DBCG trial (NCT02384733) also used the same measurement [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The new paradigm of surgery and radiotherapy has resulted in a lower complication rate. The AMAROS trial, which compared ALND with sentinel lymph node biopsy (SLNB) plus axillary radiotherapy (ART) in cN0/SLN + patients, revealed that the increase >10% in the arm circumference in the SLNB + ART group was significantly lower than that in the ALND group at 5 years (24.5% vs. 11.9%, p <0.001), with a low number of axillary recurrences in both groups (10-year cumulative incidence in ALND vs. ART: 0.93% vs. 1.82%, HR = 1.71) [ 3 ]. The prospective study of Naoum et al enrolled 1815 patients from 2005 to 2018, and the 5-year BCRL rates in the ALND group were significantly higher than those in the SLNB + RNI group (24.9% vs. 10.7%, p = 0.02) with comparable local control rates [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with early-stage breast cancer, BCS followed by WBI resulted in equivalent recurrence rates and overall survival compared with mastectomy (6, 40, 41). In addition, axillary RT has replaced axillary lymph node dissection in patients with a tumor-positive sentinel node (42). Genomic tools are utilized to identify low-risk patients with no bene t from chemotherapy (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, thanks to randomized studies such as IBCSG 23–01, Z0011 and Amaros, axillary dissection (AD) was abandoned also for patients with a positive sentinel node. But clinically positive axillary nodes were widely considered a contraindication to SNB in breast cancer in upfront surgery [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%